Evaluasi Teknis Geometri Jalan Angkut Produksi Sebagai Upaya Percapaian Target Produksi Batubara 20000 ton/bulan di Tambang Terbuka PT. Allied Indo Coal Jaya (AICJ), Perambahan, Kecamatan Talawi, Kota Sawalunto, Sumatera Barat. - Rizky Nanda Putra; Tamrin Kasim (Journals Mining Engineering : Bina Tambang, 2019)
Abstract. Based on the results of the road geometry evaluation, the following results show that the actual straight road width is between 6.2 - 10.2 m, whereas theoretically the width of the straight road must be made 9 m. The actual grade grades from Stockpile to the West Pit range from 6.98% to 15.83%. The cross slope from Pit to disposal is 4%. Superelevation figures are recommended to overcome road bends with a maximum speed of 40 km / h with a width of 12 meters curved road is 4.98%. The actual productivity before repairing the haul road using the dump truck is Hino Ranger FM 260 JD an average of 18.47 Ton / Hour. This productivity has not yet reached the production target set by PT. Alliet Indo Coal Jaya which is equal to 20000 tons / month. As for productivity after road repairs, 20.90 tons / hour. Keywords:   Geometry, Stockpile, Haul Road, Productivity, Target.